Ultrasonic Ring Array-Based Transient Triplet Differential Photoacoustic Imaging for Strong Background Removal - Wang, Guan; Wang, Bo; Ye, Tong; Wang, Congcong; Guo, Lili; Xiao, Jiaying; Chen, Zeyu (Frontiers in Materials, 2021)
Photoacoustic imaging (PAI) is a fast evolving imaging technology enabling in vivo imaging with high specificity and spatial resolution. However, due to strong background signals from various intrinsic chromospheres such as melanin, Photoacoustic imaging of targeting objects labelled by contrast agents remain a challenge. Transient triplet differential (TTD) method has shown significant potential for background free photoacoustic imaging. Here we develop a photoacoustic system using ultrasonic semicircular ring array for transient triplet differential imaging. PtOEP and black ink are used as the contrast agent and phantom of melanoma, respectively. Using TTD method, we could remove the strong background signal from black ink. The ratio between contrast agent signal and background signal is increased to about 10 times the previous. Our finding demonstrates the potential of TTD method on molecular imaging for strong background removal.